Pemberdayaan Remaja Desa Wisata Bendosari Kecamatan Plantungan Kabupaten Kendal Melalui Pelatihan Pembuatan Papan Informasi Berbahasa Inggris dan Indonesia - Ngasbun Egar; Fitri Yulianti; Siti Musarokah; Donny Anhar Fahmi (Universitas Islam Nahdlatul Ulama Jepara, 2019)
Teenagers have an important role to develop the village into a tourist village. One of the roles is to develop existing facilities and infrastructure at tourist sites. Information boards are a very important part of tourism villages’s management because it can be the information about tourist attractions, restrictions and warnings. Therefore, training and mentoring in making information boards in English and Indonesian need to be done in Bendosari Village, Plantungan District, Kendal Regency because of the limited number of information boards at tourist sites, especially in Jeglong Waterfall. The method used in the training is lecture, question and answer and practice. Participants in the training and mentoring activities for the making of this information board were the teenagers of Bendosari Village. The outcomes generated from these training activities are 1) teenagers 'understanding of the importance of information boards at tourist sites increases, 2) teenagers' understanding of the phrases used on information boards both in English and in Indonesian also increases, 3) models of information boards for tourist sites are created, and 4) nformation boards in English and Indonesian language for tourist sites are created as well